HISTORY AND EVOLUTION OF MARTIAL ARTS AND FIGHTING: A NARRATIVE REVIEW OF THE LITERATURE - Moreira, João Vitor de Souza; Molina, Camille dos Reis; Martins, Matheus Silva; Monteiro, Leonardo Olier de Souza; dos Santos, Marcelo Pereira; e Silva, André Calil; do Nascimento, Guilherme de Jesus; Novaes, Jefferson da Silva; Vianna, Jeferson Macedo; Galdino, Leonardo Hadade; Nogueira, Maria Antônia de Jesus; Pantaleão, Diogo; et al. (Seven Editora, 2025)
The history of martial arts and fighting has evolved into structured sporting and cultural expressions, so discussing these aspects is essential in order to elucidate the historical transformations, cultural impacts and contemporary manifestations of these practices. The aim of this research was to carry out a narrative review of the literature in order to ascertain how the historical and evolutionary process of martial arts and wrestling took place in different cultures and what their impacts were on the transformation of warrior practices into contemporary sporting, philosophical and cultural manifestations. A narrative literature review was carried out using the descriptors: “martial arts”, “fighting”, “history”, “origin”, ‘evolution’, “sportivization”. The search was carried out in the Scholar Google and SciELO databases. The results were discussed along three main axes: historical development, cultural impact and contemporary manifestations. The historical development of martial arts stems from issues related to power, self-defense, religious rituals and later sports practices. The cultural impact of these activities is related to the philosophical and social aspects of their regions of origin, as we can see in the discipline present in Japanese martial arts. In terms of contemporary manifestations, there has been a greater inclusion of fighting as a bodily activity capable of improving physical fitness and personal development, as well as being an important form of leisure and sporting practice. It can be concluded that martial arts have undergone major transformations over the years in line with the development of societies, where they still have a major influence as a mechanism for the physical and personal development of those who practice them. DOI: https://doi.org/10.56238/sevened2025.026-029